Redacción periodística y su influencia en los medios digitales como espacios de enseñanza y aprendizaje en los egresados de comunicación social de la Universidad Técnica de Babahoyo Extensión Quevedo, año 2022 - Orellana Vélez, Génesis Karla (2022)
Journalistic feedback is the style of writing used to report news newspapers, TV broadcasts, radio and internet. The journalistic genres are the way in which the journalist in order to capture the readers, having to be different depending on the circumstance of the news, their interest and above all, the objective of the publication. They can be: informative, interpretive and opinion. Digital media are spaces in which communication and information exchange between users of digital content is generated. In the world of digital media, having a strategy and objectives is ideal for managing communication processes with the recipient; Objectives are those who guide the actions within each channel. The fundamental role played by digital (educational) media in teaching-learning processes; are those with whom the student interacts and acquires necessary skills and competencies that help resolve any concern that arises in the student phase.